Mental Health and Substance Use Disparities Among Urban Adolescent Lesbian and Bisexual Girls. (September 2013) - Marshal, Michael P.; Dermody, Sarah S.; Shultz, Michelle L.; Sucato, Gina S.; Stepp, Stephanie D.; Chung, Tammy; Burton, Chad M.; Markovic, Nina; Hipwell, Alison E.
BACKGROUND: Sexual minority girls (SMGs) report large substance use disparities and victimization experiences, yet there is a dearth of research that focuses exclusively on SMGs.OBJECTIVE: To examine substance use and mental health disparities among SMGs and to determine whether disparities were larger for African American compared with European American girls.METHOD: Data were used from Wave 11 of the Pittsburgh Girls Study, a multiple-cohort, prospective study of urban girls. Girls for the current analysis were aged 16 to 19 years. Fifty-five percent were African American. One hundred and seventy-three (8.3%) identified as SMGs, and 1, 891 identified as heterosexual. Multiple regression analyses controlling for age, race, and parent education were conducted.RESULTS: SMGs reported a robust pattern of large disparities in externalizing, internalizing, and borderline personality disorder symptoms. There was little evidence to suggest disparities were moderated by race.CONCLUSION: SMGs and their families would benefit from intervention and prevention programs to reduce disparities among this highly vulnerable population.